Ethical Leadership: Lessons from Africa for International Management - Story, Joana; Guimarães-Costa, Nuno; e Cunha, Miguel; Kamoche, Ken; Rego, Arménio (Management international / International Management / Gestiòn Internacional, 2022)
Scholarship at the interface of ethics, leadership and organizations in Sub-Saharan Africa (SSA) is still scarce. We draw from literature about leadership in Africa to identify three research streams (functional, cultural, and critical) and use these streams to make sense of research on ethics, organizations and leadership in SSA, as well as to analyze opportunities for research. We propose four interpretative approaches allowing the advancement of research in the field of ethical leadership in SSA. More diverse research on SSA is important for it allows the development of textured theories on the context and opens possibilities for revitalizing organization theory.